Herbal Approaches to Enhance Udder Health, Milk Quantity and Quality in Lactating Dairy Cattle: A Comparative Study - Vedamurthy, Deepthi; Venkataramaiah, Malathi; Dodamani, Pramod; Kadegowda, Anil Kumar Gopalpura; Reddy, Madhura Yadava; Jolapure, Abhishek Mahadev (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
This study evaluated the efficacy of various herbal agents as post milking teat dips on somatic cell count, milk yield and milk composition in lactating dairy cattle for 28 days. A total of 25 lactating dairy HF crossbred cows of 6 to 8 years of age maintained under a loose housing system were divided into five groups each having five cows; T1 (Control fresh clean water), T2 (1% potassium iodide), T3 (Aloe vera gel), T4 (turmeric paste) and T5 (neem oil). Among the treatment groups, the group dipped with Aloe vera gel and neem oil was significantly (P≤0.05) effective in reducing somatic cell counts and increased the milk compositional parameters viz., SNF, lactose and protein. There was no consistent increase trend seen in milk yield, though there was a significant (P≤0.05) difference on days 7 and 14. On days 21 and 28, milk yield did not show any significant difference between the treatment groups. The aforementioned results primarily conclude that among the herbal agents used as teat dips, Aloe vera gel and neem oil performed better compared to other treatment groups as they contributed to improved udder health by reducing somatic cell counts and positively influenced milk composition parameters. Further, studies can be conducted to explore the bacteriological cure and teat condition improvement with these teat dips.
Keywords: Herbal agents; Milk composition; Milk yield; Somatic cell count; Teat dips